Does the use of atypical antipsychotics as adjunctive therapy in depression result in cost savings? Comparing healthcare costs and utilization between second-line treatment options. (1st November 2016) - Hassan, Amany K.; Farmer, Kevin C.; Brahm, Nancy C.; Keast, Shellie; Nesser, Nancy; Neas, Barbara R.
Abstract: Background : Several atypical antipsychotics (AAPs) are used as second-line agents for treatment resistant depression. AAPs can be expensive compared to other treatment options and can cause several side effects. Objectives : To estimate healthcare costs and utilization of AAPs compared to other second-line agents. Methods : Observational study using Medicaid claims data (2006–2011). Subjects were depression-diagnosed adult members with at least two prescriptions of antidepressant medications followed by a second-line agent. Gamma generalized linear models (GLM) produced estimates of the difference in mean expenditures among treatment groups after adjusting for individual baseline characteristics using propensity scores. Negative binomial models produced estimates of the difference in number of hospitalizations and emergency department (ED) visits. Results : A total of 3910 members received second-line treatment. Treatment groups were AAPs ( n  = 2211), augmentation agents other than AAPs ( n  = 1008), and antidepressant switching ( n  = 691). AAPs resulted in higher mean adjusted pharmacy costs and higher mean adjusted total mental health-related costs. Mean adjusted total healthcare costs and number of inpatient and ED visits were not different among treatments. Conclusion : The results show no evidence that AAPs used as second-line treatment for depression results in overall cost savings or lower inpatient and ED visits compared to other treatment strategies.